1985
DOI: 10.1063/1.335749
|View full text |Cite
|
Sign up to set email alerts
|

Photoluminescence and electrical properties of close space vapor transport GaAs epitaxial layers

Abstract: Close spaced vapor transport (CSVT) epitaxial layers have been grown under water vapor partial pressure p ranging from 5×10−2 to 5 mm Hg for source temperatures of 800 and 850 °C and a substrate temperature of 730 °C, using undoped high-purity GaAs as source material and 〈100〉 chromium doped high-resistivity GaAs as substrate. From Hall measurements, all layers were found to be n-type with a majority carrier concentration in the range of (2–3) ×1017 cm−3 and a mobility 3100–3600 cm2 V−1 s−1 as p varies from 5.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 9 publications
0
11
0
Order By: Relevance
“…However, while O has been detected in CSVT films at a concentration ~10 16 cm -3 by SIMS [26], the midgap state has only been detected by deep-level transient spectroscopy (DLTS) when O 2 was intentionally introduced into the reactor [27]. Increasing water vapor concentrations during growth have also been correlated with degraded photoluminescence [28] [4], although in our own work with electrochemical cells J sc was only degraded at very high water concentrations (>4000 ppm) [20]. The influence of oxygen on device performance merits further study.…”
Section: Device Propertiesmentioning
confidence: 99%
“…However, while O has been detected in CSVT films at a concentration ~10 16 cm -3 by SIMS [26], the midgap state has only been detected by deep-level transient spectroscopy (DLTS) when O 2 was intentionally introduced into the reactor [27]. Increasing water vapor concentrations during growth have also been correlated with degraded photoluminescence [28] [4], although in our own work with electrochemical cells J sc was only degraded at very high water concentrations (>4000 ppm) [20]. The influence of oxygen on device performance merits further study.…”
Section: Device Propertiesmentioning
confidence: 99%
“…GaAs was indeed the first material to be deposited successfully by CSVT. Epitaxial layers were obtained on GaAs (6)(7)(8)(9)(10)(11)(12)(13)(14) and on Ge (1-4, 8, 15, 16) substrates. Their growth mechanisms have been modeled (10,13) and some of their electrical properties (7-9, 13-16) (type of semiconductor, charge carrier densities, and mobilities) as well as their photoluminescence properties (1 1, 12) have been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…In order to separate material quality issues intrinsic to the CSVT process from those related to heteroepitaxy on silicon, it is useful to compare the data of Table 3 with previously published data for the CSVT growth of GaAs films on GaAs substrates. Using similar process parameters, Mimila-Arroyo et al [65] reported electron mobilities as high as 3600 cm 2 /V-s for samples doped at approximately the same donor concentrations.…”
Section: Characterization Of Csvt Gaas-on-siliconmentioning
confidence: 93%